Evaluating the Health and Hygienic Condition of Swimming Pools in Mashhad City in Different Seasons of the Year 2018 - Abdolhamid Gohari; hosein alidadi; ramAzan mirzaei (Mashhad University of Medical Sciences, 2020)
Introduction: Swimming pools are one of the most important sport and recreational areas where health tips must be followed, or adverse results would threaten the health of the whole society. Objective: The aim of this study was to identify and evaluate the health and hygienic status of the swimming pools as well as water health status in public pools in Mashhad in the first nine months of 2018. Methods: This practical research has been carried out to identify the relevant risks, as field observations for assessing the hygienic condition of indoor areas in 64 swimming pools For data collection in the present study, valid and reliable questionnaires of general information and human resources (14 question), health assessment (37 questions), and water quality control of Mashhad's swimming pools were used. Parametric analysis of variance was utilized for normal data, and non-normal data were analyzed by Kruskal-Wallis nonparametric test by considering P <0.05. Results: The results of the evaluation of water quality by health centers indicated that the desirability amount of the residual chlorine, water pH, water temperature, water turbidity, microbial thermophile coliforms, heterotrophic bacteria, and water chemical quality was 86%, 96%, 95.44%, 92.44%, 96.49%, 94.96%, and 95.31%, respectively. Amount of the residual chlorine, water turbidity, and heterotrophic bacteria was below the expected level of 95%. The outcomes of the tests administered by Mashhad health and hygiene centers (supervision organization), and pool managers' self-control examinations revealed that the results of water pH, water temperature, thermophile coliform, and water chemical tests were in total accordance with standards (P <0.05). Conclusion: The results showed that most of the health risks were related to the residual chlorine, turbidity, and microbial contamination of water by heterotrophic bacteria. Training swimmers and hygiene culture development have a pivotal role in controlling health risks